O modelo das competências profissionais no mundo do trabalho e na educação: implicações para o currículo - Neise Deluiz (Boletim Técnico do Senac, 2001)
Analyzes the competences model in the work world in the context of internationalization of the capitalism and of the companies productive restructuring. Detach the focus of the competences in the work administration and the implications of its adoption for the workers. Points the circumstances of the incorporation of the competences model in the education and its influence in the Brazilian education reform. Discusses the different conceptions and forms of implementation of the competences model in the Professional Education politics in the country and analyzes the theoretical-conceptual patterns that guide the identification and construction of competences. Finally, address the formulation and organization of the curriculum.